MAIN OPERATIVE TREATMENT STRATEGIES FOR FRACTURES OF THE LUMBAR SPINE — A REVIEW OF THE CURRENT LITERATURE - Maciej Zachara; Paulina Dybiak; Mateusz Bartoszek; Patryk Harnicki; Erwin Grzegorzak; Oliwia Krawczyk; Jakub Minas; Adrian Morawiec; Paweł Słoma; Rafał Pelczar; Mikołaj Grodzki; Weronika Emilia Zubrzycka; et al. (International Journal of Innovative Technologies in Social Science, 2026)
Lumbar spine fractures are a clinically significant cause of spinal instability, neurological impairment, and long-term functional disability. While many injuries can be treated conservatively, operative management is frequently required in selected cases. The objective of this narrative review is to summarize and critically analyze current evidence regarding the main surgical strategies used in treatment of lumbar spine fractures, with particular emphasis on indications for surgery, classification systems, and operative techniques.A narrative review of the literature was performed using the PubMed, Scopus, and Google Scholar databases. Articles published between 2013 and 2024 were screened using predefined keywords related to lumbar spine fractures and operative management. Original research articles, review papers, and clinical guidelines focusing on surgical treatment in adult patients were included.The reviewed literature indicates that classification systems such as the AO Spine Thoracolumbar Classification and the Thoracolumbar Injury Classification and Severity Score (TLICS) play a big role while guiding the decisions in connection with patient specific factors. Posterior instrumentation remains the most commonly used operative strategy due to its versatility and reliability. Anterior and combined anterior–posterior approaches are reserved for selected complex cases with significant anterior and posterior column compromise, while minimally invasive techniques are increasingly utilized due to decreased complications and morbidity rate.In conclusion, operative management of lumbar spine fractures should be individualized and guided by fracture morphology, neurological status, and patient-specific factors. Although posterior fixation remains the prime surgical treatment option, evolving techniques continue to refine operative strategies, underscoring the need for further studies.